Islamic Work Ethics in Modern Organizations: The Mediating Role of Organizational Culture - Ibrahim, Mahdani; Idris, Sofyan (Heca Sentra Analitika, 2023)
This study aims to explore and elucidate the perception and implementation of Islamic Work Ethics (IWE), Organizational Culture (OC), and Job Involvement (JI) within Sharia-compliant banks. This study comprises a threefold examination. Firstly, it scrutinizes the immediate influence of IWE on JI. Secondly, it delves into the mediating role of OC in the relationship between IWE and JI. Lastly, it explores the direct influence of IWE on OC and the subsequent impact of OC on JI. The research cohort consisted of 151 employees from Bank Rakyat Indonesia (BRI) Syariah (now Bank Syariah Indonesia (BSI)) in Banda Aceh, Indonesia. Primary data were collected through the distribution of questionnaires and analyzed using a Structural Equation Modeling (SEM) framework with the Application Analysis of Moment Structures (AMOS). The findings revealed that: (1) IWE exerts a relatively modest direct impact on JI, (2) OC emerges as a pivotal factor mediating the influence of IWE on JI, and (3) IWE has a direct and significant effect on OC, subsequently affecting JI. These multifaceted findings are comprehensively explored and discussed in the ensuing discourse.